2020
DOI: 10.5944/openpraxis.12.4.1139
|View full text |Cite
|
Sign up to set email alerts
|

What About Reuse? A Study on the Use of Open Educational Resources in Dutch Higher Education

Abstract: Extensive research has taken place over the years to examine the barriers of OER adoption, but little empirical studies has been undertaken to map the amount of OER reuse. The discussion around the actual use of OER, outside the context in which they were developed, remains ongoing. Previous studies have already shown that searching and evaluating resources are barriers for actual reuse. Hence, in this quantitative survey study we explored teachers’ practices with resources in Higher Education Institutes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Different studies were concluded in several countries, including Canada [99], China [101]. Netherlands [95], Australia, and others.…”
Section: Discussion and Gapsmentioning
confidence: 99%
“…Different studies were concluded in several countries, including Canada [99], China [101]. Netherlands [95], Australia, and others.…”
Section: Discussion and Gapsmentioning
confidence: 99%
“…Much has already been published on the financial and social benefits of OER (Menzli et al, 2022;Hilton et al, 2014;Baas & Schuwer, 2020). However, we found that there is no unambiguous glossary for several other terms used in debates and projects.…”
Section: Introductionmentioning
confidence: 88%
“…While videos and images are reused without modifications, instructors often make adaptations for course units. Presentations and assignments are material types that are predominantly self-created and not reused by others (Baas and Schuwer 2020). By reusing OER, instructors aim to improve the quality of their teaching, but they want to avoid too much effort for adaptations and remixing (Baas, Admiraal, and van den Berg 2019).…”
Section: Usage Studies Of Oermentioning
confidence: 99%